(3QSGdI GdbUQ hGdJNjjQ aj GdSaQs - (3eMeO Hf MSjf GdMGQKj GdgeOGfj GdYGedj, HgGA GdOjf , J (B1031 (3g` s
(3ChdgG (B:s
(3hHYO ENJda ai eSFdI bUQ GdUdGI ai GdSaQ gd gh hGLH Ch dG jLhR GdYOhd Yfg s
(3BNQgG (B:s
(3Hd GdCOdI GdJi CRGOJ ceG jTgO Hg GdEfUGa hGddg hdi GdJhajb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B19s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B102s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(369) s
Keywords: (3GdeLGejYs